Developing a framework for community-based sexual health interventions for youth in the rural setting: Protocol for a participatory action research study - Heslop, C.; Burns, Sharyn; Lobo, R.; McConigley, R. (BM J Group, 2017)
Introduction: There is limited research examining community-based or multilevel interventions that address the sexual health of young people in the rural Australian context. This paper describes the Participatory Action Research (PAR) project that will develop and validate a framework that is effective for planning, implementing and evaluating multilevel community-based sexual health interventions for young people aged 16-24 years in the Australian rural setting. Methods and analysis: To develop a framework for sexual health interventions with stakeholders, PAR will be used. Three PAR cycles will be conducted, using semistructured one-on-one interviews, focus groups, community mapping and photovoice to inform the development of a draft framework. Cycle 2 and Cycle 3 will use targeted Delphi studies to gather evaluation and feedback on the developed draft framework. All data collected will be reviewed and analysed in detail and coded as concepts become apparent at each stage of the process. Ethics and dissemination: This protocol describes a supervised doctoral research project. This project seeks to contribute to the literature regarding PAR in the rural setting and the use of the Delphi technique within PAR projects. The developed framework as a result of the project will provide a foundation for further research testing the application of the framework in other settings and health areas. This research has received ethics approval from the Curtin University Human Research and Ethics Committee (HR96/2015).